Effect of Substituents on the Homopolymerization Activity of Methyl Alkyl Diallyl Ammonium Chloride - Xu Jia; Xiujuan Zhang; Wenhui Peng; Kui Yang; Xiao Xu; Yuejun Zhang; Guixiang Wang; Xianping Tao (Molecules, 2022)
Among nitrogen-containing cationic electrolytes, diallyl quaternary ammonium salt is a typical monomer with the highest positive charge density, which has attracted the most attention, especially in the research on homopolymers and copolymers of dimethyl diallyl ammonium chloride (DMDAAC), which occupy a very unique and important position. In order to improve the lipophilicity of substituted diallyl ammonium chloride monomers under the premise of high cationic charge density, the simplest, most direct, and most efficient structure design strategy was selected in this paper. Only one of the substituents on DMDAAC quaternary ammonium nitrogen was modified by alkyl; the substituents were propyl and amyl groups, and their corresponding monomers were methyl propyl diallyl ammonium chloride (MPDAAC) and methyl amyl diallyl ammonium chloride (MADAAC), respectively. The effect of substituent structure on the homopolymerization activity of methyl alkyl diallyl ammonium chloride was illustrated by quantum chemical calculation and homopolymerization rate determination experiments via ammonium persulfate (APS) as the initiator system. The results of quantum chemistry simulation showed that, with the finite increase in substituted alkyl chain length, the numerical values of the bond length and the charge distribution of methyl alkyl diallyl ammonium chloride monomer changed little, with the activation energy of the reactions in the following order: DMDAAC < MPDAAC < MADAAC. The polymerization activities measured by the dilatometer method were in the order DMDAAC > MPDAAC > MADAAC. The activation energies Ea of homopolymerization were 96.70 kJ/mol, 97.25 kJ/mol, and 100.23 kJ/mol, and the rate equation of homopolymerization of each monomer was obtained. After analyzing and comparing these results, it could be easily found that the electronic effect of substituent was not obvious, whereas the effect of the steric hindrance was dominant. The above studies have laid a good foundation for an understanding of the polymerization activity of methyl alkyl diallyl ammonium chloride monomers and the possibility of preparation and application of these polymers with high molecular weight.